4CPS-140 Current status of clinical trials for Alzheimer's disease. (24th March 2020) - Rodriguez, A; Navarrete-Rouco, ME; Acin, P; Ponce, M; Jorques, M; Ferrandez-Quirante, O; Espona, M
Abstract : Background and importance: Alzheimer's disease (AD) is a progressive neurodegenerative process caused by an accumulation of the Aβ amyloid peptide. Aim and objectives: The objective of this study was to describe the current status of clinical trials (CT) for AD in our hospital pharmacy service and to analyse the investigational drugs. Material and methods: An observational descriptive retrospective study was carried out in a tertiary academic hospital. All active CT in the neuropsychology service from 1 January 2014 to 31 March 2019 were reviewed. Collected data were total number of CT; total number of included patients; demographic data; total number of CT classified by CT status (active/closed); clinical trial phase; therapeutic targets (reduction of amyloid plaques (AP)/precursor amyloid peptide (PAP) attack/inhibition of GLYT1 transporter/selective antagonism of 5-HT6 receptor/partial selective agonism of α7 nicotinic receptor); administration route (oral/intravenous/subcutaneous); clinical trials with results; and type of result (positive/negative). Results: Twelve CT were analysed involving a total of 59 patients (mean 5 patients per clinical trial (rank 0–8)), 34 (57.6%) women with a mean age of 77.4 years (95% CI 71.5–84.7). Six (50.0%) CT were active; 3 (25.0%) CT were phase II trials and 9 (75.0%) were phase III trials. Therapeutic targets were reduction in AP 5 (41.7%), attack of PAP 3 (25.0%), inhibition of GLYT1 transporter 1 (8.3%), selective antagonism of 5-HT6 receptor 2 (16.7%), partial selective agonism of α7 nicotinic receptor 1 (8.3%); route of administration oral 7 (58.3%), intravenous 1 (8.3%) or subcutaneous 4 (33.3%); and 3 (25.0%) CT had results, all of which were negative (3 (100%)). Conclusion and relevance: The highest number of active CT were phase III trials. Only 25% of CT had results and all were negative. Almost 60% of CT studied oral administration, which was patients' preference. There were a total of five therapeutic targets but more than 40% of the CT evaluated the reduction in APs. Based on these results, we should rethink the research on Alzheimer's disease before continuing to develop clinical trials with the same therapeutic target. References and/or acknowledgements: No conflict of interest.